The Effectiveness of the Integrated Referral System (SISRUTE) on Obstetrics and Neonatal Referral Indicators at RSUD dr. Doris Sylvanus Palangka Raya - Legawati, Legawati; Utama, Nang Randu; Purba, Maria Magdalena; Yeyentimalla, Yeyentimalla; Aryani, Vissia Didin; Nurfianto, Sigit (Formosa Journal of Science and Technology, 2024)
This study aims to assess the effectiveness of SISRUTE on obstetric and neonatal referral indicators, at RSUD dr Doris Sylvanus Palangka Raya Raya. The research method used in this study is the mix method (qualitative and quantitative method). Data collection techniques are carried out by observation, in-depth interview, Focus Group Discussion (FGD), documentation and triangulation. This research will be conducted at RSUD dr Doris Sylvanus Palangka Raya and RSUD Mas Amsyar Kasongan. The study was conducted for 3 months (August to October 2023). As result, Obstetrics and Neonatal Referral Indicators can be assessed from the response of obstetrian and neonatal referral cases received treatment at the hospital. The Integrated Referral System (SISRUTE) has not made obtetry and neonatal referral cases a priority, so it still gets the same treatment (in response time).